PENGARUH PENDEKATAN CONCRETE PICTORIAL ABSTRACT BERBANTUAN TANGRAM TERHADAP PENINGKATAN KEMAMPUAN SPATIAL SENSE SISWA SEKOLAH DASAR: (Penelitian Quasi Eksperimen pada Kelas IV SD Negeri 4 Nagrikaler di Kabupaten Purwakarta) - Hami, Nadya Berchmans; Rahayu, Puji; Rosmana, Primanita Sholihah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Tangram-assisted Concrete Pictorial Abstract (CPA) learning approach on improving students' spatial sense abilities in elementary schools. This research uses a quasi-experimental research method with a nonequivalent control group design. The research sample consisted of 46 students consisting of 23 experimental class students who applied the Concrete Pictorial Abstract learning approach assisted by Tangram and 23 control class students who applied the scientific learning approach at SDN 4 Nagrikaler. This research collects data using tests, namely pretest and posttest, as well as documentation as non-test data. The results of the research showed that the increase in spatial sense abilities of students who received learning using the tangram-assisted CPA approach was better than students who received learning using the scientific approach. This research also provides a positive influence in using the tangram-assisted CPA approach on students' spatial sense abilities. So the tangram-assisted CPA approach can be an alternative used to improve students' spatial sense abilities and can be used in learning, especially for grade 4 students, on flat shapes. Keywords: Tangram, Concrete Pictorial Abstract (CPA) Approach, Spatial Sense Ability.